Accuracy of free-hand positioned patient specific implants (PSI) in primary reconstruction after inferior and/or medial orbital wall fractures. (October 2021) - Probst, Florian Andreas; Cornelius, Carl-Peter; Otto, Sven; Malenova, Yoana; Probst, Monika; Liokatis, Paris; Haidari, Selgai
Abstract: Background: To assess the accuracy with which CAD/CAM-fabricated patient-specific titanium implants (PSI) are positioned for inferior and/or medial orbital wall reconstruction without the use of intraoperative navigation. Methods: Patients who underwent a primary reconstruction of the orbital walls with PSI due to fractures were enrolled in this retrospective cohort analysis. The primary outcome variables were the mean surface distances (MSD) between virtually planned and postoperative PSI position and single linear deviations in the x-, y- and z-axis at corresponding reference points. Secondary outcome variables included demographic data, classification of orbital wall defects and clinical outcomes. Results: A total of 33 PSI (orbital floor n = 22; medial wall, n = 11) were examined in 27 patients. MSD was on a comparable level for the orbital floor and medial wall (median 0.39 mm, range 0.22–1.53 mm vs. median 0.42 mm, range 0.21–0.98 mm; p = 0.56). Single linear deviations were lower for reconstructions of the orbital floor compared to the medial wall (median 0.45 vs. 0.79 mm; p < 0.05). There was no association between the occurrence of diplopia and the accuracy level (p = 0.418). Conclusions: Free-hand positioning of PSI reaches a clinically appropriate level of accuracy, limiting the necessity of navigational systems to selected cases. Highlights: Accuracy with which CAD/CAM-fabricated patient-specific titanium implants are positioned for orbital wall reconstruction. Geometric deviation between virtually planned and postoperative PSI position. Freehand positioning of PSI for orbital wall reconstruction is accurate. Navigation systems are not mandatory for orbital wall reconstruction.